2010
DOI: 10.1016/j.scr.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantified proarrhythmic potential of selected human embryonic stem cell-derived cardiomyocytes

Abstract: To improve proarrhythmic predictability of preclinical models, we assessed whether human ventricular-like embryonic stem cell-derived cardiomyocytes (hESC-CMs) can be selected following a standardized protocol. Also, we quantified their arrhythmogenic response and compared this to a contemporary used rabbit Purkinje fiber (PF) model. Multiple transmembrane action potentials (AP) were recorded from 164 hESC-CM clusters (9 different batches), and 12 isolated PFs from New Zealand White rabbits. AP duration (APD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 37 publications
3
72
0
1
Order By: Relevance
“…As an alternative to the comparison of the drug effects with published results from other laboratories, two recent studies have demonstrated concordance between hPSC-derived cardiomyocytes and conventional, well validated, rabbit and canine ex vivo Purkinje fiber models, which are commonly used as follow-up assays [15,16]. Using microelectrodes to measure the transmembrane action potential of hPSC-derived cardiomyocytes, Jonsson et al [15] determined parameters such as reverse use dependence, triangulation of the action potential, and short-term variability of repolarization to assess drug-induced arrhythmic events.…”
Section: Hpsc-derived Cardiomyocytes In Toxicity Testingmentioning
confidence: 98%
See 1 more Smart Citation
“…As an alternative to the comparison of the drug effects with published results from other laboratories, two recent studies have demonstrated concordance between hPSC-derived cardiomyocytes and conventional, well validated, rabbit and canine ex vivo Purkinje fiber models, which are commonly used as follow-up assays [15,16]. Using microelectrodes to measure the transmembrane action potential of hPSC-derived cardiomyocytes, Jonsson et al [15] determined parameters such as reverse use dependence, triangulation of the action potential, and short-term variability of repolarization to assess drug-induced arrhythmic events.…”
Section: Hpsc-derived Cardiomyocytes In Toxicity Testingmentioning
confidence: 98%
“…Using microelectrodes to measure the transmembrane action potential of hPSC-derived cardiomyocytes, Jonsson et al [15] determined parameters such as reverse use dependence, triangulation of the action potential, and short-term variability of repolarization to assess drug-induced arrhythmic events. Importantly, for the comparison with the Purkinje fiber model, all data collection for this study was performed at the same laboratory, using the same experimental setup, and under the same conditions.…”
Section: Hpsc-derived Cardiomyocytes In Toxicity Testingmentioning
confidence: 99%
“…75 Cardiac grafts could possibly contribute to all 3 fundamental arrhythmia mechanisms, namely automaticity, 18 reentry, 39 and triggered activity. 76 As mentioned before, conflicting results have been obtained regarding whether these cardiac grafts cause arrhythmias. 49-53 However, it remains a potential issue to be further explored.…”
Section: Arrhythmiamentioning
confidence: 99%
“…Caffeine normally triggers an increase in cytosolic Ca 2+ whereas ryanodine decreases the levels of Ca 2+ , therefore, the maintenance of the balance of Ca 2+ levels in cardiomyocytes derived from pluripotent stem cells may not be identical to the balance in normal adult cardiomyocytes. It is also notable that while cardiomyocytes derived by targeted differentiation from embryonic stem cells were shown to alleviate arrhythmia when transplanted in injured myocardium; other authors have demonstrated that cardiomyocytes derived from hESC may possess inherent pro-arrhythmic potential [76,77]. Non-fatal ventricular arrhythmias were observed in macaques that have received intracardially cardiomyocytes derived from differentiation of hESC [59].…”
Section: Cardiomyocytes Derived By Differentiation Of Esc and Ipscmentioning
confidence: 99%